1994
DOI: 10.1051/lait:1994422
|View full text |Cite
|
Sign up to set email alerts
|

Whey crossflow microfiltration using an M14 Carbosep membrane: influence of initial hydraulic resistance

Abstract: 5ummary -Membrane hydraulic resistance (Rm) for the same nominal M14 Carbosep membrane (pore diameter 0.14 um) was found to vary significantly from 0.85 ± 0.05 to 1.22 ± 0.09 1012 m-1. Pretreated whey microfiltration experiments carried out using these new membranes resulted in shorter operating time and lower protein transmission for the low Rm membranes. When the same membrane was used new, irreversibly fouled or cleaned (Rm = 1.14, 2.48and 1.261012 m-1 respectively) fouling evolution was positively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The hydraulic resistance values obtained under the TMP operating regimens were not statistically different, except for R rev which was lower (P < 0.05) for T2, compared with T1 and T3. Some studies have demonstrated that at high TMP, a more compact and compressed deposit layer structure occurs, which is responsible for the increase in reversible fouling (Gésan et al, 1994;Samuelsson et al, 1997;Cari et al, 2000). Also, Miller et al (2014) reported that constant permeation flux operation caused the continuous accumulation of fouling on the membrane (i.e., increasing total hydraulic resistance), compared with constant TMP where the fouling deposit remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…The hydraulic resistance values obtained under the TMP operating regimens were not statistically different, except for R rev which was lower (P < 0.05) for T2, compared with T1 and T3. Some studies have demonstrated that at high TMP, a more compact and compressed deposit layer structure occurs, which is responsible for the increase in reversible fouling (Gésan et al, 1994;Samuelsson et al, 1997;Cari et al, 2000). Also, Miller et al (2014) reported that constant permeation flux operation caused the continuous accumulation of fouling on the membrane (i.e., increasing total hydraulic resistance), compared with constant TMP where the fouling deposit remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…s -1 ; ∆P = 1.5 × 10 5 Pa for 1 h. After a water rinse the irreversible fouled membrane resistance, R if WPC , was calculated from the pure water flux measurement [15]. The cleaning cycle of the fouled UF membrane was performed at: T = 50 o C; v = 4.0 m .…”
Section: Cleaning Experimentsmentioning
confidence: 99%
“…In several studies, microfiltration has been investigated regarding the relationship of flux, wall shear stress, and fouling, particularly in the area of protein fractionation as a function of overall membrane properties and average processing conditions (Marshall et al, 1993;Brans et al, 2004). Gésan et al (1994) established a relationship between membrane resistance against water permeation and the fouling behavior for filtration of whey. The higher the initial water flux, the more pronounced the extent of deposit formation.…”
Section: Introductionmentioning
confidence: 99%